2000
DOI: 10.1046/j.1365-2559.2000.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐3/CPP32 immunoreactivity and its correlation with frequency of apoptotic bodies in human prostatic carcinomas and benign nodular hyperplasias

Abstract: Based on our results, the number of apoptotic bodies was not correlated with the caspase-3 expression and there was no relationship between caspase-3 expression and Gleason score. However, the number of apoptotic bodies was significantly higher in cases with intermediate (Gleason score 5-7) and high-grade (Gleason score 8-10) PCAs than cases with BPH and low-grade PCAs (Gleason score 2-4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…However, some nuclear staining was also found. This is in line with other studies, in which a cytoplasmic location of pro-caspase 3 was found [7,28]. Donoghue et al [4] also described punctuate cytoplasmic staining, and they associated this pattern with mitochondrial localisation of procaspase 3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, some nuclear staining was also found. This is in line with other studies, in which a cytoplasmic location of pro-caspase 3 was found [7,28]. Donoghue et al [4] also described punctuate cytoplasmic staining, and they associated this pattern with mitochondrial localisation of procaspase 3.…”
Section: Discussionsupporting
confidence: 92%
“…In stomach cancer, there was a tendency for a positive correlation between pro-caspase 3 expression and the deoxynucleotidyl-transferase (TdT) mediated deoxy uridine triphosphate nick end labelling (TUNEL) labelling index [11]. However, no correlation between pro-caspase 3 expression and apoptosis was found in lung and prostate cancer [28,29,31,37].…”
Section: Discussionmentioning
confidence: 99%
“…Filtration with a 0.2-m (data not shown) or 0.45-m filter caused the loss of nucleolin immunoreactivity, indicating that the nucleolin was not secreted as soluble protein; instead, it was associated with particles of a size greater than 0.45 m. However, a significant amount of nucleolin passed through a 0.8-m filter, excluding the possibility that the immunoreactivity was the result of the presence of intact cells (which are Ͼ10 m in diameter) that were not collected by centrifugation. These apoptosis-induced particles are of a size that is consistent with "apoptotic bodies" that are often observed during apoptosis in cultured cells and in vivo (43)(44)(45)(46). These apoptotic bodies are commonly detected by TUNEL staining for fragmented DNA (46); therefore, we prepared slides from the medium of untreated or UV-irradiated U937 cells and analyzed them for TUNEL and nucleolin immunoreactivity.…”
Section: Identification Of Nucleolin In Extracellular Apoptosis-inducedmentioning
confidence: 66%
“…This excessive apoptosis can be caused by a number of conditions including inflammation, autoimmune disease, ischemic injury, and cancer. There is evidence that the presence of apoptotic cells or bodies can be an important diagnostic or prognostic marker for several types of cancer (45,(62)(63)(64) and detection of circulating apoptotic material (e.g. nucleosomes or nucleic acids) in serum has been proposed as a non-invasive method to detect the presence of malignancy or to evaluate therapeutic response in cancer patients receiving chemotherapy or radiation (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, lack of association between the accumulation of caspase-3 and apoptotic index has been reported for many cancer types, although the antibody used did not allow to discriminate between precursor and active forms of this protease. 14,18,20,39 Recently assessment of apoptosis in human breast tissue using antibody against the active capsase-3 in relation to tumor histopathological characteristics was performed. 40 The authors did not find an association between AI and tumor size, but observed a correlation between AI measured as expression of active caspase-3 and AI derived from morphological data.…”
Section: Discussionmentioning
confidence: 99%